2007
DOI: 10.1097/mlr.0b013e31812da820
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Healthcare-Seeking Behavior for Urinary Incontinence and the Impact of Socioeconomic Status

Abstract: Community-living older women with UI problem are less likely to seek professional help than their male counterparts, but more likely to be treated after a health professional is consulted. Patients' socioeconomic status can affect physician behavior and ultimately, their receipt of treatment of UI, especially for women. Current efforts to promote awareness and quality-of-care of UI among older adults should account for gender and other sociodemographic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 31 publications
6
47
1
Order By: Relevance
“…Incontinence was associated with the fourth largest QOL score decreases in these health domains, consistently larger than several serious chronic conditions such as cardiovascular disease and diabetes to name a few, suggesting that physical and vitality domains were significantly impacted as well. Management of incontinence has been evaluated in past studies of managed Medicare populations [1,3,16]. Two of these studies [1,3] reported that only 41-56% of respondents with UI problems discussed incontinence with their doctors, and that only 50-56% of these UI respondents received treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Incontinence was associated with the fourth largest QOL score decreases in these health domains, consistently larger than several serious chronic conditions such as cardiovascular disease and diabetes to name a few, suggesting that physical and vitality domains were significantly impacted as well. Management of incontinence has been evaluated in past studies of managed Medicare populations [1,3,16]. Two of these studies [1,3] reported that only 41-56% of respondents with UI problems discussed incontinence with their doctors, and that only 50-56% of these UI respondents received treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Effective incontinence management strategies and treatments exist, including behavioral techniques, bladder training and other exercise therapy to strengthen pelvic floor muscles, pharmacotherapy, devices, and surgery [13]. Nevertheless, few patients discuss incontinence with their doctors or receive treatment [1,3,[14][15][16]. Early detection and treatment may benefit the aging population, potentially preventing the onset of complications that can progress to more serious incontinence, nursing home placement, and adversely impact health-related QOL.…”
Section: Introductionmentioning
confidence: 97%
“…However, a limitation of this question about not seeking care was the small number of women who responded. A US study [20] reported that incontinent women were less likely to seek professional help for their UI compared with incontinent men (46.2% vs. 55.7%) but were more likely to receive treatment (54.8% vs. 51.4%). For women, the predicted rate of receiving treatment decreased with a decreasing level of education.…”
Section: Discussionmentioning
confidence: 99%
“…However, Li et al revealed that Community-living older women (age 65 and older) with urinary incontinence problem are less likely to seek professional help than their male counterparts, but more likely to be treated after a health professional is consulted [29]. In this study, moderate or severe OAB or SUI had more of an impact on the quality of life in women than in men.…”
Section: Discussionmentioning
confidence: 46%